The Effect of Humility, Leadership, and Person-Job Fit on Innovative Work Behavior With Organizational Justice as an Intervening Variable at Employees PT. Sinar Sosro Tanjung Morawa - Yolanda Putri RW.N*; Muhammad Irfan Nasution (Riwayat: Educational Journal of History and Humanities, 2023)
Success in product sales is inseparable from the quality of the performance of members or employees of PT. Sinar Sosro  Tanjung Morawa through the level of satisfaction at work and by highlighting the latest innovations. This research was conducted to determine the effect of humility leadership (X1) and person job fit (X2) on innovative work behavior (Y) with organizational justice (Z) as a mediating variable. The population of this research is all employees of PT. Sinar Sosro Tanjung Morawa about 180 people with a sample of 60 people by proportional random sampling from all departments. The data analysis technique used in this research is PLS-SEM (Structural Equation Modeling). There are two group stages in analyzing SEM-PLS, including a measurement model (Outer Model) and a structural model (Inner Model).